Research work presentation with Cards Diagram - Munir, Saima (International Multidisciplinary Research Journal, 2019)
In this paper, we proposed appropriate diagram to present and converted research work or data into information base of cards is called Cards diagram. It provide meaningful summary and very helpful for researchers/ students to decide and define research work in meetings. The concept of a diagram within diagram is being introduced the first time through it. The logic of a conceptual model, modelling language, meta-model and tool also explained with details.